Fake prophecy and polluted sacraments : ecclesiastical and imperial reactions to Montanism - Tabbernee, William, 1944- (Vigiliae Christianae, Supplements, 2007)
During the four centuries of its existence (ca. 165-550), Montanism, an early-Christian prophetic movement, stirred up considerable controversy. Known to its adherents as the 'New Prophecy,' its opponents viewed it as a ' fake prophecy' with 'polluted sacraments.' Accused of introducing novelty and heresy into Christianity. Montanism, in the post-Constantinian era, was also persecuted by Christian emperors. This book identifies all known opponents of Montanism, analyzes and classifies the various charges leveled against Montanism, and describes the methods used to counteract and ultimately destroy the movement. Also described are the ways in which the Montanists reacted to the opposition against them, revealing that the picture painted of the New Prophecy by its opponents was grossly distorted. Fake Prophecy and Polluted Sacraments provides an insightful case-study of the treatment of a minority Christian movement by Church and State both before and after 'catholic' Christianity became the official religion of the Roman Empire.